Ketorolac eye drops reduce inflammation and delay re-epithelization in response to corneal alkali burn in rabbits, without affecting iNOS or MMP-9 - Lima,Tiago Barbalho (2015)
Purposes: To assess the effects of 0.5% ketorolac tromethamine without preservatives on the expression of iNOS and MMP-9 in alkali burn ulcers. Methods: Twelve eyes of 120-day-old male rabbits were treated (TG) every 6 h with 0.5% ketorolac tromethamine and 12 other eyes were treated with saline solution (CG), immediately after the occurrence of ulcers by 1 M sodium hydroxide (NaOH). Re-epithelialization was monitored using fluorescein every 6 h. After 24 h, six corneas (n=6) of each group were collected (M1). The others (n=6) were collected after reepithelialization (M2). At both moments, the inflammatory infiltrate and the conditions of the newly formed epithelium were histologically analyzed. iNOS and MMP-9 were evaluated by immunohistochemistry. Results: Mean epithelialization time in TG was 55 ± 0.84 h. In CG, it was 44 ± 1.06 h (p=0.001). At M1, corneas of TG had lower inflammatory exudation compared with (p <0.001). At M2, TG revealed discrete inflammatory exudation (p>0.05) and lower numbers of epithelial layers compared with CG. The mean iNOS in stromal cells did not differ in TG over both moments compared with CG (p>0.05) At M2, the central corneal region expressed more iNOS in both groups compared with the peripheral region. No significant differences were observed in iNOS scores of epithelial immunostaining between the groups and across M1 and M2 (p=0.69). Epithelial immunostaining scores for MMP-9 did not differ in TG compared with CG (p=0.69). The average immunostaining score of MMP-9 in stromal cells showed no differences between groups or moments. There was no correlation between immunostaining of iNOS and MMP-9 or between the amount of inflammatory cells and immunostaining of iNOS. Conclusions: Use of 0.5% keratolac tromethamine reduced inflammation and delayed reepithelialization in a cornea alkali burn model without impacting the expression of iNOS or MMP-9.